2015
DOI: 10.1007/s11325-015-1190-2
|View full text |Cite
|
Sign up to set email alerts
|

Delayed neutrophil apoptosis mediates intermittent hypoxia-induced progressive heart failure in pressure-overloaded rats

Abstract: The results of this study demonstrated that IH aggravates LV remodeling and heart dysfunction in rats with pre-existing HF. Delayed neutrophil apoptosis, which was revealed in HF rats following exposure to IH, contributed to the exacerbation of myocardial damage and progression of heart dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
(35 reference statements)
1
6
0
1
Order By: Relevance
“…As showed in the current study, rats with CIH had significantly higher LV‐end‐systolic volume, decreased both fractional shortening and ejection fraction, which are generally associated with ventricular remodeling. Consistent with our results, cardiac dysfunction and LV remodeling were reported to show a significant decrease in LV fractional shortening and ejection fraction in rats treated with intermittent hypoxia (IH) for 4 weeks . In another study, OSA patients with hypertension had decreased LVEF, and FS compared with the nonhypertensive OSA group, suggesting that hypertension acts as a catalyst on CIH‐induced LV systolic dysfunction.…”
Section: Discussionsupporting
confidence: 88%
“…As showed in the current study, rats with CIH had significantly higher LV‐end‐systolic volume, decreased both fractional shortening and ejection fraction, which are generally associated with ventricular remodeling. Consistent with our results, cardiac dysfunction and LV remodeling were reported to show a significant decrease in LV fractional shortening and ejection fraction in rats treated with intermittent hypoxia (IH) for 4 weeks . In another study, OSA patients with hypertension had decreased LVEF, and FS compared with the nonhypertensive OSA group, suggesting that hypertension acts as a catalyst on CIH‐induced LV systolic dysfunction.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the nitric oxide synthase gene deletion via gene knockout showed that the number of apoptotic myocardial cells was decreased and LVEF was increased after myocardial infarction, suggesting that the improvement of cardiac function in heart failure is closely related to the decrease of frequency of myocardial cell apoptosis away from the infarcted zone, and the myocardial cell apoptosis away from the infarcted zone may be one of the important reasons for cardiac remodeling and development of heart failure after myocardial infarction (20). In heart failure, the hypoxia-ischemia of myocardial cells, oxidative stress, inflammatory factors, mechanical load and neuroendocrine factors, can induce myocardial cell apoptosis (21,22), but which factor dominates in heart failure remains unclear, and the specific mechanism of myocardial apoptosis and relationship need to be further studied. At present, animal experiments and autopsy of patients with heart failure have shown that myocardial cell apoptosis exists in heart failure, but the proportion of apoptosis varies in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia can lead to oxidative stress and overproduction of reactive oxygen species. Reactive oxygen species can also activate nuclear transcriptional factors, including NF-kB and HIF-1α [17] , which stimulates production of inflammatory mediators such as interleukin (IL)-6 [18] , as we observed in this model.…”
Section: Discussionmentioning
confidence: 89%